Critical analysis of Comparative Law. Interview with Tom Ginsburg - Bendezú Medina, Samuel H. (2016)
In this interview, the professor Tom Ginsburg addresses Comparative Law, the conditions for its study, its influence in capitalism, as well as his comparative studies over the constitutions, especially, of Latin American ones. He also addresses the conceptions that societies have about the relationship between Law and society, the moment of the creation of a Constitution, the factors involved in it and the perception of the judges and their decisions.